A Novel Constant Volume System for Determining Transport Properties in Polymeric Membranes - Leszczynski, Peter Jr. (Université d'Ottawa / University of Ottawa, 2023)
Membrane gas separation became an industrial reality in the late 1970s with Monsanto's first commercial asymmetric hollow fiber membrane modules. Innovations in membrane separations result from new materials that exhibit an improved permeability and are more selective than their predecessors, with materials commonly compared to the "upper bound line." Accurate determination of the three transport properties which characterize a membrane, permeability (P), diffusivity (D), and solubility (S), is thus of great interest to exceed the current upper bound line. Also, proper characterization of membrane materials enables enhancing current commercial membrane processes or allows for new applications. All three transport properties, P, S, and D, can be determined using a single dynamic gas permeation experiment in a constant volume (CV) system, commonly called the time-lag method. This work presents the next-generation CV system that utilizes the two-tank volume concept, namely a reference volume and a working volume. Compared to the previous iteration, the pressure in the reference volume can be reduced to the anticipated pressure in the working volume after initiating the gas permeation experiment. This allows monitoring of the pressure decay in the working volume (i.e., gas permeation into the membranes) using a high-resolution differential pressure transducer (DPT) right after initiating the experiment. The new system's operation is demonstrated by simultaneous monitoring of the upstream pressure decay and the downstream pressure rise during the time-lag experiments using a polyphenylene oxide (PPO) membrane. The values determined using the pressure decay method are compared to those determined using the downstream method to identify any limitations still present in the current iteration of the CV system. To set a reliable benchmark value to compare against, the downstream receiver was redesigned, and an optimal configuration was identified, which was associated with negligible resistance to gas accumulation and, thus, a minor error in the experimental time lag downstream from the membrane. Furthermore, a temperature enclosure was built to minimize errors caused by the constant temperature assumption during the time lag analysis. Additionally, the temperature-controlled enclosure allows for transport properties temperature dependence to be quantified by determining the activation energy of permeability, diffusion, and the enthalpy of solution for a given gas/polymer system.
Keywords: Membrane Characterization; Constant-volume; Polymer; Polymeric; Constant Volume; time-lag